2012
DOI: 10.1007/s00784-012-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early bilateral mandibular first molar extraction on condylar and ramal vertical asymmetry

Abstract: This article investigates the effects of early bilateral mandibular molar teeth extraction that has never been investigated in the literature. The present study showed that the lengths of the condylar, ramal, and condylar plus ramal height were less in the study group than in a well-matched control group of without extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
2
20
0
8
Order By: Relevance
“…Our study examined this hypothesis because the patient's head position is not an assessment criterion when using CBCT, and the findings showed that the investigators interested in condylar asymmetry should revise the 3% CAI threshold value of Habets et al, 7 as reported previously. 11,18 In addition, previous studies 13,16,17,32 using panoramic films also reported that CAI values in normal occlusion groups were over 7%, within the limitations of those films.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our study examined this hypothesis because the patient's head position is not an assessment criterion when using CBCT, and the findings showed that the investigators interested in condylar asymmetry should revise the 3% CAI threshold value of Habets et al, 7 as reported previously. 11,18 In addition, previous studies 13,16,17,32 using panoramic films also reported that CAI values in normal occlusion groups were over 7%, within the limitations of those films.…”
Section: Discussionmentioning
confidence: 87%
“…21,22 Most previous studies 9, [12][13][14][15][16][17]23 investigating the relationship between condylar asymmetry and various malocclusions were carried out using panoramic films. Although this technology has an acceptable cost-benefit ratio because of its minimal radiation exposure, it suffers from limitations similar to those derived from the conventional cephalometric analyses including magnification, distortion, and superimposition of anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los adultos, las mediciones verticales de cóndilo y rama mandibular, utilizando la misma fórmula de Bezuur con punto de corte entre +3 % y -3 %, probaron asimetría solamente en 8 de 100 cráneos analizados radiográficamente, concluyendo que la diferencia en las medidas condilares puede ser una de las principales causas de la patología del aparato estomatognático (Boratto et al) y es evidente que el desbalance oclusal, puede inducir a cambios morfológicos condilares, como una respuesta adaptativa de la mandíbula, resultado del remodelado óseo y la función muscular (Wang et al, 2011). En una comparación entre pacientes con ausencia de primer molar inferior bilateral, y pacientes con dentición completa, se muestra que las longitudes de la rama mandibular, y el cón-dilo fueron menores en el grupo de estudio, aunque no de manera estadísticamente significativas (Halicioglu et al, 2013;Halicioglu et al, 2014). En cadáveres, hay mediciones clíni-cas similares a las de este estudio, pero muestran que no existe una correlación entre estas variables y la talla y el índice de masa muscular, cuando se analizaron 20 medidas antropométricas, pero resalta la importancia de dichas mediciones al momento de los procedimientos quirúrgicos para la reconstrucción mandibular, especialmente la zona condilar y la cavidad glenoidea (Gnecco et al, 2013).…”
Section: Discussionunclassified
“…Las asimetrías en el eje izquierda-derecha existen, y se deben establecer como una normalidad dentro de la población y las estructuras craneofaciales, ya que estas se establecen en la fase embrionaria a través de la expresión de genes Nodal, Lefty, y Pitx2, donde además, el desequilibrio muscular o dentario influyen fuertemente en cambios en las estructuras (Muñoz et al, 2011), sobretodo los cóndilos mandibulares que están en constante función y actividad por los músculos masticadores. Por otra parte, factores como la extracción de los primeros molares, muestra que las longitudes de los cóndilos, ramas mandibulares y su índice sumatorio son menores (Halicioglu et al, 2013).…”
Section: Apcunclassified